Peroxide treatment of feather meal for finishing cattle - Löest, C.A.; Coetzer, C.M.; Titgemeyer, Evan C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Heifers (756 lb, 312 head) were used in a finishing study to evaluate the effects of peroxide-treated feather meal on animal performance and carcass characteristics. Diets contained 3.0% of peroxide-treated or untreated feather meal, and were fed ad libitum. Treatment of feather meal with hydrogen peroxide increased in situ protein degradabilities by 56%, but did not significantly alter feed intake or feed efficiencies. Although not statistically different, gains were 2.1% greater for heifers fed peroxide-treated feather meal. Hot carcass weights also averaged 6 pounds heavier for heifers fed diets containing peroxide-treated feather meal. Marbling tended to be lower, but carcasses grading USDA Choice tended to be higher for heifers fed diets containing peroxide-treated feather meal.
Keywords: Beef; Peroxide; Feather meal; Finishing cattle